Comparing impacts of meditation training in focused attention, open monitoring, and mindfulness‐based cognitive therapy on emotion reactivity and regulation: Neural and subjective evidence from a dismantling study. (19th February 2022) - Brown, Kirk Warren; Berry, Daniel; Eichel, Kristina; Beloborodova, Polina; Rahrig, Hadley; Britton, Willoughby B.
Abstract: Commonly conducted mindfulness‐based trainings such as Mindfulness‐based Stress Reduction (MBSR) and Mindfulness‐based Cognitive Therapy (MBCT) highlight training in two key forms of meditation: focused attention (FA) and open monitoring (OM). Largely unknown is what each of these mindfulness practices contributes to emotional and other important training outcomes. This dismantling trial compared the effects of structurally equivalent trainings in MBCT, FA, and OM on neural and subjective markers of emotional reactivity and regulation among community adults, with the aim to better understand which forms of training represent active ingredients in mindfulness trainings. Participants with varying levels of depressive symptoms were randomized to one of the three trainings. Before and after each 8‐week training, N = 89 participants completed a modified version of the Emotional Reactivity and Regulation Task while electroencephalographic (EEG) and self‐reported emotional responses to negative, positive, and neutral photographic images were collected. Examination of EEG‐based frontal alpha band asymmetry during passive viewing (reactivity) and active regulation phases of the task showed that FA and MBCT trainings produced significant leftward hemispheric shifts in frontal alpha asymmetry, commonly associated with a shift toward approach‐based positive affect. Self‐reported emotional responses to negative images corroborated these results, suggesting salutary changes in both emotional reactivity and regulation. OM training had limited beneficial effects, restricted to the subjective outcomes. The findings suggest that MBCT may derive its greatest benefit from training in FA rather than OM. Discussion highlights the potential value of FA training for emotional health. Abstract : In the first report comparing emotion‐relevant impacts of focused attention meditation (FA), open awareness meditation (OM), and Mindfulness‐based Cognitive Therapy (MBCT) among those with depressive symptoms, we show that FA and MBCT produced leftward hemispheric shifts in frontal alpha asymmetry, consistent with approach‐based positive affect, during an emotion reactivity and regulation task. Self‐reported emotional responses to negative images corroborated these results. The findings highlight the potential value of FA and MBCT training for emotional health.